India and the COVID-19 vaccine - Karthyayani Priya Satish (Taylor & Francis Group, 2022)
The recent article "Exploring the COVID-19 vaccine candidates against SARS-CoV-2 and its variants: where do we stand and where do we go?" published on December 2 is thought provoking. The authors highlight critical disparities in the manufacture and distribution of COVID-19 vaccines although over 350 COVID-19 vaccine candidates are reported to be in the preclinical and clinical development phase. The history of vaccine research and production in India is as ancient as the history of vaccines themselves. Interestingly, vaccine manufacture that was once monopolized by India, declined in its productivity and stature, primarily for the lack of a strategic vision. The recent approval of COVAXIN, designed and developed in India, for emergency use by the World Health Organization is significant for a huge and diverse developing country such as India, especially to transform a weak regulatory system, and enhance public trust.